Visible light scattering from micron scale silicon nitride structures - McCloskey, David (Trinity College (Dublin, Ireland). School of Physics, 2012)
Light scattering from complex and irregular shapes is responsible for many optical effects in nature. Butterfly wings change colour when viewed from different angles, due to a complex nanoscale scattering structure. Ice halos are formed by light scattering from hexagonal prisms formed from ice crystals. Radar scattering from leaves of trees is commonly modelled as scattering from thin disks. By reproducing and modifying these nature inspired structures numerous applications such as electronic displays, colour changing paint, and anti-counterfeiting have been found. This thesis deals with light scattering from micron scale scatterers defined in a 400nm layer of silicon nitride Si3N4.With illumination from visible light these particles are in the Mie scattering regime and are referred to as "small particles". Shapes with different cross sections are defined in the thin layer using electron beam lithography (EBL) and inductively coupled plasma etching (ICP). Visible light is scattered strongly both in plane and out of plane by the structures. The intensity distribution in the near-field (Fresenel region) can be controlled by controlling the cross sectional shape of the scatterer. A simple imaging technique is outlined to map the properties of the near-field intensity distribution from the far-field. This is a simple, non-invasive technique, which gives a lot of information about the scatting without the need for SNOM or more complicated near-field imaging techniques. The technique works particularly well in this case as the near-field intensity distribution of interested is formed primarily from propagating light. The experimental results are compared with a full 3D finite element method (FEM) model of the near-field intensity.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin